Joint analysis of Dark Energy Survey Year 3 data and CMB lensing and cosmological constraints - Chang, C.; Omori, Y.; Baxter, E. J.; Doux, C.; Choi, A.; Pandey, S.; Alarcon, A.; Alves, O.; Amon, A.; Andrade-Oliveira, F.; Bechtol, K.; Becker, M. R.; et al. (Amer Physical Soc, 2023)
Cross-correlations of galaxy positions and galaxy shears with maps of gravitational lensing of the cosmic microwave background (CMB) are sensitive to the distribution of large-scale structure in the Universe. Such cross-correlations are also expected to be immune to some of the systematic effects that complicate correlation measurements internal to galaxy surveys. We present measurements and modeling of the cross-correlations between galaxy positions and galaxy lensing measured in the first three years of data from the Dark Energy Survey with CMB lensing maps derived from a combination of data from the 2500 deg2 SPT-SZ survey conducted with the South Pole Telescope and full-sky data from the Planck satellite. The CMB lensing maps used in this analysis have been constructed in a way that minimizes biases from the thermal Sunyaev Zel'dovich effect, making them well suited for cross-correlation studies. The total signal-to-noise of the cross-correlation measurements is 23.9 (25.7) when using a choice of angular scales optimized for a linear (nonlinear) galaxy bias model. We use the cross-correlation measurements to obtain constraints on cosmological parameters. For our fiducial galaxy sample, which consist of four bins of magnitude-selected galaxies, we find constraints of omega m 1/4 0.272 thorn 0.032 pffiffiffiffiffiffiffiffiffiffiffiffiffiffi-0.052 and S8 equivalent to sigma 8 omega m=0.3 1/4 0.736 thorn 0.032 -0.028 (omega m 1/40.245 thorn 0.0-0.04426 and S8 1/40.734 thorn 0.035 -0.028 ) when assuming linear (nonlinear) galaxy bias in our modeling. Considering only the cross-correlation of galaxy shear with CMB lensing, we find omega m 1/4 0.270 thorn 0.043 -0.061 and S8 1/4 0.740 thorn 0.034 -0.029 . Our constraints on S8 are consistent with recent cosmic shear measurements, but lower than the values preferred by primary CMB measurements from Planck.